THE INFLUENCE OF PRODUCT QUALITY, PROMOTION, AND BRAND AWARENESS ON PURCHASE DECISIONS FOR MIXUE ICE CREAM & TEA - Salsa Bila, Meisya Noor; Rachmawati, Erny; Rahayu, Tri Septin Muji; Utami, Restu Frida (Derivatif : Jurnal Manajemen, 2024)
This research aims to analyze the influence of product quality, promotion and brand awareness on purchasing decisions for Mixue products in Purwokerto. The research method used is quantitative, and the data analysis method is descriptive statistics. Samples were taken using the Accidental Sampling technique, based on the lemeshow formula, 96.4 respondents were obtained, while the results of obtaining respondents were 125 respondents. Data collection used questionnaires distributed offline. From the data that has been obtained and processed using SPPS26, the results show that product quality has a negative and insignificant effect on purchasing decisions. While the promotion and brand awareness variables have a positive and significant effect on purchasing decisions.Keywords: Product quality, Promotion, Brand awareness, Purchasing Decisions